Alternative Methods for Endovascular and Hybrid Bleeding Control - Hörer, Tal; T McGreevy, David (Journal of Endovascular Resuscitation and Trauma Management, 2023)
Puncture site or vascular access bleeding may be managed with open or endovascular methods. In this paper, we shortly describe alternative methods for endovascular and hybrid bleeding control.